Mereformasi Akal Budi: Teologi Analitik, Skolastisisme Reformed, dan Peran Dogmatik Kristen di Sepanjang Masa - Wilson Jeremiah (STT Reformed Injili Internasional, 2022)
Doing theology and constructing Christian dogmatics always rely on the good use of reason and logical and critical thinking. Analytic theology is an intellectual movement in the twenty-first century that emphasizes the significance of employing tools from analytic philosophy and modern logic in doing theology. However, analytic theology in general has not been successful in producing theological works which adhere to the rules and standards in the science of theology. This paper discusses an “analytic”-theological model from the sixteenth- and seventeenth-century tradition called Reformed scholasticism, and lists some excellent characteristics from it. By providing a historical and analytical survey of the primary and secondary sources related to Reformed scholasticism, this author demonstrates how the Reformed scholastic theological tradition that is confessional, systematic, dialogical, catholic, contextual, and educative inspires contemporary and future theologians to keep on constructing Christian dogmatics that is rational but not rationalistic, open-minded but not compromising truth, and interdisciplinary yet integrative.